Application of activated carbon from empty fruit bunch (EFB) for mercury [Hg(II)] removal from aqueous solution - Kabbashi, Nassereldeen Ahmed; Mirghani, Mohamed Elwathig Saeed; Jamil, Ili Nadirah (Academic Journals, 2011)
Mercury is a heavy metal and is used widely in the industry, making it a global problem. It accounts for approximately 70% of man-made emissions. Activated carbon was found to be efficient for the adsorption of Hg(ll) in aqueous solution. The characterization of Hg(ll) uptake showed that the mercury binding is dependent on initial pH, agitation speed, amount of dosage and also the interaction between pH and contact time. From the experiment, the initial concentration of mercury was set to be 1.6 mg/L. It was found that the minimum residual concentration of mercury was 0.0075 mg/L (99.53%) at the condition of pH 6.5, agitation speed of 100 rpm, contact time of 70 min and AC dosage of 20 mg. This value was considered acceptable as it met the requirement of the Department of Environment, Malaysia.